Efficient Capital Markets, Inefficient Firms: A Model of Myopic Corporate Behavior - Stein, Jeremy C. (Quarterly Journal of Economics, 1989)
This paper develops a model of inefficient managerial behavior in the face of a rational stock market In an effort to mislead the market about their firms' worth, managers forsake good investments so as to boost current earnings. In equilibrium the market is efficient and is not fooled: it correctly conjectures that there will be earnings inflation, and adjusts for this in making inferences. Nonetheless, managers, who take the market's conjectures as fixed, continue to behave myopically. The model is useful in assessing evidence that has been presented in che “myopia” debate. It also yields some novel implications regarding firm structure and the limits of intergation.